2011
DOI: 10.1116/1.3628602
|View full text |Cite
|
Sign up to set email alerts
|

Embedding a carbon nanotube across the diameter of a solid state nanopore

Abstract: A fabrication method for positioning and embedding a single-walled carbon nanotube (SWNT) across the diameter of a solid state nanopore is presented. Chemical vapor deposition (CVD) is used to grow SWNTs over arrays of focused ion beam (FIB) milled pores in a thin silicon nitride membrane. This typically yields at least one pore whose diameter is centrally crossed by a SWNT. The final diameter of the FIB pore is adjusted to create a nanopore of any desired diameter by atomic layer deposition (ALD), simultaneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Besides, Stein's group demonstrated that SWCNTs could be embedded in a nanopore (Jiang et al, 2010 ). Golovchenko, Branton, and colleagues reported an in situ growth method to embed SWCNTs across nanopores (Sadki et al, 2011 ). These provide new alternative approaches to minimize electrode size as diameter of the thinnest SWCNT is only 0.3 nm (Zhao et al, 2004 ).…”
Section: Other Nanopore Sequencingmentioning
confidence: 99%
“…Besides, Stein's group demonstrated that SWCNTs could be embedded in a nanopore (Jiang et al, 2010 ). Golovchenko, Branton, and colleagues reported an in situ growth method to embed SWCNTs across nanopores (Sadki et al, 2011 ). These provide new alternative approaches to minimize electrode size as diameter of the thinnest SWCNT is only 0.3 nm (Zhao et al, 2004 ).…”
Section: Other Nanopore Sequencingmentioning
confidence: 99%
“…For this reason, some groups have explored advanced functionalization of nanopore devices by designing more complex structures. These structures include multilayered membranes, metallized dielectric membranes with or without molecular coatings, and membranes equipped with nanoelectrodes . In all these cases, the architecture of these advanced nanopore devices involve at least one conductive metallic film.…”
Section: Introductionmentioning
confidence: 99%
“…Another example incorporates small molecules that bind to specific short sequences of DNA, allowing spatial determination of identifying regions rather than individual nucleotides [60]. Finally, several groups are pursuing nanopore devices with incorporated nanoelectrodes [61, 62, 63, 64] to measure sequences using tunneling currents rather than trans-membrane ionic current. Each of these methods shows great potential for success.…”
Section: Future Prospectsmentioning
confidence: 99%